Salt Stress Modulates the Landscape of Transcriptome and Alternative Splicing in Date Palm (Phoenix dactylifera L.) - Xu, Zhongliang; Zhang, Ning; Fu, Haiquan; Wang, Fuyou; Wen, Mingfu; Chang, Hailong; Wu, Jiantao; Abdelaala, Walid Badawy; Luo, Qingwen; Li, Yang; Li, Cong; Wang, Qinnan; et al. (Frontiers in Plant Science, 2022)
Date palm regards as a valuable genomic resource for exploring the tolerance genes due to their ability to survive under the severer condition. Although a large number of differentiated genes was identified in date palm respond to salt stress, the genome-wide study of alternative splicing (AS) landscape under salt stress conditions remains unknown. In the current study, we identified the stress-related genes through transcriptomic analysis in order to characterize their function under salt. A total of 17,169 genes were differentially expressed under salt stress condition. Gene expression analysis confirmed that the salt overly sensitive (SOS) pathway genes, such as PdSOS2;1, PdSOS2;2, PdSOS4, PdSOS5, and PdCIPK11 were involved in the regulation of salt response in date palm, which is consistent with the physiological analysis that high salinity affected the Na+/K+ homeostasis and amino acid profile of date palm resulted in the inhibition of plant growth. Interestingly, the pathway of ‘Spliceosome’ was enriched in the category of up-regulation, indicating their potential role of AS in date palm respond to salt stress. Expectedly, many differentially alternative splicing (DAS) events were found under salt stress condition, and some splicing factors including PdRS40, PdRSZ21, PdSR45a, and PdU2Af genes were abnormally spliced under salt, suggesting that AS-related proteins might be participated in regulating the salt stress pathway. Moreover, the number of differentially DAS-specific genes was gradually decreased, while the number of DEG-specific genes was increased with prolonged salt stress treatment, suggesting that AS and gene expression could be distinctively regulated in response to salt stress. Therefore, our study highlighted the pivotal role of AS in the regulation of salt stress and provided novel insights for enhancing the resistance to salt in date palm.